Yeast as a Tool to Study Signaling Pathways in Mitochondrial Stress Response and Cytoprotection. (2nd February 2012) - Ždralević, Maša; Guaragnella, Nicoletta; Antonacci, Lucia; Marra, Ersilia; Giannattasio, Sergio
Abstract : Cell homeostasis results from the balance between cell capability to adapt or succumb to environmental stress. Mitochondria, in addition to supplying cellular energy, are involved in a range of processes deciding about cellular life or death. The crucial role of mitochondria in cell death is well recognized. Mitochondrial dysfunction has been associated with the death process and the onset of numerous diseases. Yet, mitochondrial involvement in cellular adaptation to stress is still largely unexplored. Strong interest exists in pharmacological manipulation of mitochondrial metabolism and signaling. The yeast Saccharomyces cerevisiae has proven a valuable model organism in which several intracellular processes have been characterized in great detail, including the retrograde response to mitochondrial dysfunction and, more recently, programmed cell death. In this paper we review experimental evidences of mitochondrial involvement in cytoprotection and propose yeast as a model system to investigate the role of mitochondria in the cross-talk between prosurvival and prodeath pathways.